2022
DOI: 10.1007/s12033-022-00643-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Glycolysis Prevents the Cerebral Infarction Progression Through Decreasing the Lactylation Levels of LCP1

Abstract: Cerebral infarction (CI), also known as ischemic stroke, has a high incidence rate and mortality rate. The purpose of this study was to investigate the potential effect and mechanism of Lymphocyte cytosolic protein 1 (LCP1) in the CI progression. The middle cerebral artery occlusion (MCAO) treated rats and oxygen–glucose deprivation/reoxygenation (OGD/R) stimulated PC12 cells were used to establish CI model in vivo and in vitro. The cell proliferation and apoptosis was determined by CCK-8 assay and flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“… 22 Recent investigations have also revealed the potential of LCP1 as a therapeutic target for cerebral ischemia–reperfusion injury. 23 In our study, LCP1 exhibited low expression in normal corneas but showed significant upregulation in CNV corneas, possibly because of the low density of immune cells at immune-privileged sites. 24 However, following corneal alkali burn, the influx of immune cells, particularly neutrophils, migrated to the injured area, potentially influencing LCP1 expression.…”
Section: Discussionsupporting
confidence: 43%
“… 22 Recent investigations have also revealed the potential of LCP1 as a therapeutic target for cerebral ischemia–reperfusion injury. 23 In our study, LCP1 exhibited low expression in normal corneas but showed significant upregulation in CNV corneas, possibly because of the low density of immune cells at immune-privileged sites. 24 However, following corneal alkali burn, the influx of immune cells, particularly neutrophils, migrated to the injured area, potentially influencing LCP1 expression.…”
Section: Discussionsupporting
confidence: 43%
“…As shown by previous studies, the lactylation modification could enhance protein stability. 18,38 Herein, we performed the half-life profile of RUNX2 and identified that mutation of K176 site shortened the half-life time of RUNX2, indicating that the lactylation of RUNX2 at K176 site affected the stability of RUNX2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that hypoxia enhances β-catenin lactylation to improve its stability in colorectal cancer [ 44 ]. Decreased lactylation of lymphocyte cytosolic protein 1 (LCP1) caused by glycolysis inhibition reduces LCP1 stability during cerebral infarction progression [ 45 ]. Moreover, methyltransferase-like 3 (METTL3) lactylation enhances METTL 3 protein stability in intracerebral hemorrhage [ 46 ].…”
Section: Discussionmentioning
confidence: 99%